Practical risk management in the construction industry - Edwards, Leslie (Engineering management., 1995)
Provides an overview of the risk management procedures that are applicable generally to commercial organizations. The book also deals with the risks that might arise particularly in construction and, by the use of practical examples, how those risks can be managed.